Eksekusi Jaminan Fidusia Berasaskan Keadilan Pasca Putusan Mahkamah Konstitusi No. 18/PUU-XVII/2019 - Iwan Riswandie (Scholar Center, 2021)
Ease of execution is based on protection for creditors to be able to guarantee repayment of debtor obligations at the risk of default or bad credit with the existence of a Fiduciary Certificate, of course, the creditor's position is protected in an execution activity in the event of a breach of promise (default) from the debtor in the main agreement or additional agreements. who use the fiduciary guarantee institution instrument. This decision from the Constitutional Court in a legal perspective that there is legal protection by carrying out the principle of balance from the parties carrying out a legal act is that within a framework of creditors and debtors, they must receive equal and balanced treatment in accordance with the rights and obligations as wellas the risks in the resulting situation so that justice which is the main purpose of the law itself can run well. This paper examines the implications of this decision in the principle of justice in the framework of the balance of protection between debtors and creditors. The method used is normative juridical with a statutory approach and a conceptual approach. At the conclusion of this paper, the Constitutional Court's decision which provides conditions regarding the execution of fiduciary guarantees based on the Fiduciary Guarantee Certificate will certainly result in unfavorable conditions for creditors if problems occur in the future. it is necessary to apply in order to ensure the direction of protection in the event of a breach of contract/default, in the future to ensure legal certainty and maximum protection for the parties in a more balanced manner, the revision of the Fiduciary Guarantee Law needs to be put forward